(NbESEDY OB OPERE I NE TOL_KO(B.(NdIRIVERI(B.(NkOMPOZITORI(B.(NmUZYKANTY(B.(NrEVISSERI(B.(NuPRAWLENCY(B.s (NmONOGRAFIQs - (Na(B.(Np(B.(NmATMUSAEWI^s ((NsANKT(B-(NpETERBURGs (NlAN_s (NpLANETA MUZYKIs, 2024)
(NpERED WAMI(B-(NSBORNIK INTERW_@ IZWESTNOGOMUZYKAL_NOGO VURNALISTA(B.(NOBOZRAWATELQ I KRITIKA aLEKSANDRA mATMUSAEWI^A(B.s
Keywords: (NMONOGRAFIQs